New species and records of Awas Löbl (Coleoptera: Staphylinidae: Pselaphinae) from China, with notes on the biology of the genus - Yin, Zi-Wei (Zootaxa, 2017)
A new species of the arnylliine ant-loving beetle genus Awas Löbl, A. helii Yin, sp. n., collected with Ectomomyrmex ants in Sichuan, SW China, is described and illustrated. The new taxon externally resembles A. kayan Yin & Li from Hunan, central China, but can be readily separated by the different forms of the pronotum and elytra, and details of the aedeagal structures. New collecting data for Awas loebli Yin & Li in eastern China, as well as some notes on the biology of the genus are provided.